Geochemical effects of soil cover remediation on sulphide-rich tailings at the Kristineberg mine, northern Sweden - Carlsson, Erik (Luleå tekniska universitet, 2000)
Remediation of mine waste by the application of till cover is one of the more common methods used in Sweden to prevent oxidation of sulphide-rich minerals. Although the general conclusion from Swedish state-of-the-art field studies is that dry covers may be effective, they are expensive to construct. Further investigations are also needed to understand the processes occurring in till covered waste deposits. The Kristineberg mining area has been chosen as the main field site for the research program MiMi (Mitigation of the environmental impact of mining waste) funded by the Foundation for Strategic Environmental Research (MISTRA). MiMi focuses on finding new and improved methods to mitigate the environmental problems related to mining operations and disposal of mining waste. An extensive sampling programme was carried out in Kristineberg during 1998 and 1999. The Kristineberg mine is a Boliden mine, located within the Skellefte ore field. It is a Zn-Cu deposit developed in the 1940s and still in production. This thesis consists of three papers outlining the geochemical conditions prevailing in tailings Impoundment 1 at the Kristineberg mine, after remediation by applying till cover. The impoundment investigated was in use until the early 1950s and it was remediated in 1996. Two different remediation methods have been used; in the area with a shallow groundwater table 1.0 m of till was used to raise the groundwater table above the tailings. In other areas, with a deeper groundwater table, a sealing layer consisting of a 0.3 m thick layer of a compacted clayey till underlying a 1.5 m thick protective cover of unspecified till was used. Field studies include sampling of solid tailings, saturated tailings pore water as well as pore water from the vadose zone. Laboratory investigations consist of a five-step sequential extraction on solid tailings samples. Pre-remediation oxidation has resulted in a zonation of the tailings with an upper oxidised zone above unoxidised tailings. Just below the oxidation front, there is ...